Sensory quality of instant noodles made with rice-dehulled mungbean flour and cassava starch - Bautista, Michael Lopez
Sensory quality of instant noodles made with various levels of rice-dehulled mungbean flour as substitute for wheat flour was studied. The levels of substitution used were 0%, 10%, 20%, 30%, 40%, and 50%. The proportion used for the flour was 70:30 (rice to dehulled mungbean). Preliminary studies conducted indicated that soaking in temperature-controlled (40°C) water for 5 hours was the best dehulling method in terms of yield of dehulled mungbeans obtained. Consumer tests were conducted using 24 untrained panelists. Nine-point hedonic scales were used to evaluate the sensory characteristics of the products. Results indicated that instant noodles that is acceptable to consumers may be produced using 40% rice-dehulled mungbean flour substituted for wheat flour. The noodle produced has the following characteristics: color = 5.97 (1=white; 9=cream); color lightness = 5.96(1=very dark; 9=very light); overall flavor-rate = 5.58(1=very bland; 9=very strong); beany flavor = 3.96 (1=none; 9=very strong); smoothness = 6.08(1=very tough; 9=very smooth); hardness = 4.00 (1=very soft; 9=very hard); and, chewiness = 4.88 (1=not very chewy; 9=very chewy). Verification studies conducted confirmed the results of previous experiments.